STUDENTS' METACOGNITION PROFILE BASED ON SOLO TAXONOMY AT RELATIONAL AND EXTENDED ABSTRACT LEVELS - Rahayu, Sofy Gustini; Setialesmana, Depi; Prabawati, Mega Nur (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
The aim of this research is to evaluate students' metacognitive abilities based on the SOLO taxonomy at the relational and extended abstract levels. This study adopts a qualitative research approach with a descriptive research method. Data collection techniques include tests and unstructured interviews. Data analysis techniques, following the Miles and Huberman model, involve data reduction, data display, and conclusion drawing. The results showed that subjects at the relational and extended abstract levels performed all metacognitive activities, but the indicators achieved in solving HOTS problems on arithmetic progression varied. Subject SR-1 was able to perform planning indicators, but with errors, could monitor correctly, and performed evaluation indicators, but with errors. Subject SR-2 was able to plan correctly, could monitor but with errors, and performed evaluation indicators correctly. Subject SR-3 was able to perform planning, monitoring, and evaluation indicators correctly. Subject SR-4 was able to perform planning indicators, but with errors, could monitor correctly, and performed evaluation indicators, but with errors. Subjects SEA-1 and SEA-2 were able to perform planning, monitoring, and evaluation indicators correctly.